Power and Statebuilding in the Anglo-Norman World: An Overview - Judith Ann Green (Tabularia)
This paper explores, in the context of the Anglo-Norman world, some of the characteristics implicit in ideas of the state: relatively fixed frontiers, a sovereign authority with the power to maintain justice, raise taxes and deploy armies, and to command the allegiance of its inhabitants. Normandy and England are considered both separately and together as an “empire”. New research areas and themes relating to power and statebuilding are considered: the role of the ruler’s wife, ritual and display, the architectural context of power, and of the importance of cities, especially London. The need for a wider approach to the history of power away from the history of kings, including lords and ecclesiastics, is stressed, and developments within a British context, in Wales and Scotland, are briefly considered. The paper concludes by emphasizing the fragility of developments: statebuilding was not consistent or inevitable. Twelfth-century Normandy itself illustrates some of the ambiguities of defining states and statebuilding in this era.